Hubungan Self-Compassion dengan Resiliensi pada Mahasiswa Tahun Akhir di FIP UNP - Annisah, Rasty; Nurfarhanah, Nurfarhanah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research was motivated by several final year students who had low resilience due to low self-compassion. When final year students are faced with difficult situations, they tend to be hard on themselves by judging, criticizing and even blaming themselves for their shortcomings. The aim of the research is to describe self-compassion and resilience in final year students along with the implications for counseling services. This research uses a quantitative approach, correlational descriptive method. The population in this study consisted of 234 final year students from the class of 2019 at the Faculty of Education, Padang State University, with a sample of 148 students. The sample selection in this study used proportional random sampling technique. Data collection used self-compassion instruments and resilience instruments with a Likert scale model. Research data was analyzed using descriptive statistics and Pearson product moment correlation techniques to determine the relationship between self-compassion and resilience in final year students. The research results revealed that self-compassion in final year students was in the high category, while resilience in final year students was in the high category. Counseling services that counselors can provide to final year students to maintain and improve the quality of self-compassion and resilience include individual counseling services and group guidance services with the topic of tips on maintaining and honing self-compassion abilities and tips on increasing confidence in one's abilities.